EFFECT OF GOOD CORPORATE GOVERNANCE, FINANCIAL DISTRESS, AND FINANCIAL PERFORMANCE ON TIMELINESS OF FINANCIAL STATEMENTS REPORTING - Mardyana, Rosyida (Jurnal Ilmiah Mahasiswa FEB, 2014)
This  study  was  aimed  to  test  empirically  whether  Good  Corporate Governance  (audit committee and managerial ownership),  financial distress, and financial performance (profitability and liquidity) affect the timeliness of financial reporting on go public companies  listed  in Indonesian Stock Exchange. The data were  the  annual  financial  statements  of  companies  listed  in  Indonesia  Stock Exchange  (IDX).  Slovin’s  formula was  used  to  select  the  sample  of  220  firm-years  from  2011  to  2012.  The  data  were  analysed  using  logistic  regression analysis. The  results  indicated  that  p-values  of  audit  committee  (AC),  financial distress (FD), and  liquidity (CR) ≤ 0.05. These meant that audit committee (AC), financial distress (FD), and  liquidity (CR) significantly affected  the  timeliness of financial  statements  reporting.  Whereas,  the  logistic  regression  analysis  of managerial  ownership  (MO)  and  profitability  (ROA)  indicated  p-value  ≥  0.05, meaning that the two factors did not significantly affect the timeliness of financial statements of the go public companies.Keyword:  Timeliness,  Audit  Committee,  Managerial  Ownership,  Financial Distress, Profitability, Liquidity